2005
DOI: 10.1097/01.sla.0000186337.83407.ec
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hyperparathyroidism, Cognition, and Health-Related Quality of Life

Abstract: Surgical treatment of PHPT is a viable option for patients with laboratory diagnosed, "nonclassic" PHPT. Formal NP testing and evaluation of HRQL are useful tools that may assist physicians in choosing whom to refer for parathyroidectomy. Further longitudinal study of NP functioning and HRQL in patients with laboratory diagnosed PHPT is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(96 citation statements)
references
References 73 publications
1
87
0
8
Order By: Relevance
“…The prevalence of these abnormalities is not well defined due to the lack of rigorous evaluation of these symptoms in most studies, a small number of studies, and wide variation in the instruments used to assess the psycho-cognitive manifestations (66).…”
Section: Neuropsychiatric Manifestationsmentioning
confidence: 99%
“…The prevalence of these abnormalities is not well defined due to the lack of rigorous evaluation of these symptoms in most studies, a small number of studies, and wide variation in the instruments used to assess the psycho-cognitive manifestations (66).…”
Section: Neuropsychiatric Manifestationsmentioning
confidence: 99%
“…The impact of asymptomatic PHPT on neurocognitive function/QOL Neurological and neuropsychiatric symptoms have been described in classical PHPT [Coker et al 2005;Fitz and Hallman, 1952], but it remains unclear to what extent they are present in the mild form of PHPT seen commonly today. Neurological and neuropsychiatric symptoms are especially difficult to define and investigate in mild PHPT.…”
Section: Consequences Of Untreated Asymptomatic Phptmentioning
confidence: 99%
“…Some studies showed that a successful PTx can have positive effects on different domains of quality of life such as increased energy levels and improved physical as well as emotional well-being (26,27,28). However, other studies found no evidence of a positive change in depression scales when comparing PTx patients with patients who underwent orthopedic surgery (29).…”
Section: Introductionmentioning
confidence: 99%